THERAPY FOR IRREGULAR MENSTRUATION WITH ACUPUNTURE AND HERBAL PEGAGAN (CENTELLA ASIATICA (L.)) - Prayuni, Evin Dwi; Imandiri, Ario; Adianti, Myrna (Journal of Vocational Health Studies, 2018)
Background : Menstruation is bleeding periodic scale and cyclical from uterus extrication (deskuamasi) endometrium. Menstruation bleeding is complex interaction result wich involve hormone system and body system, that are hypothalamus, hypofisis, ovarium and uterus. Every woman has different menstruation cycle. The causes of irregular menstruation are genetic and bad habit life. While according to TCM, irregular menstruation is Yue Jing Bu Tiao. Purpose: To knowing the effect of acupuncture therapy and point of Guanyuan (CV 4), Shenshu (BL 23), Sanyinjao (SP 6) and Shenmen (HT 7). Method: Therapy was given 12 times, 3 times every week. Herbal therapy wich given was pegagan (Centella asiatica (L)) with dose 0,3 and consumed everyday after eat. Result : therapy that used acupuncture and herbal in irregular menstruation case showing menstruation cycle change, that was menstruation cycle became shorter from 76 days to 41 days. Conclusion : acupuncture therapy on point of Guanyuan (CV 4), Shenshu (BL 23), Sanyinjao (SP 6), Shenmen (HT 7), and pegagan herbal (Centella asiatica (L)) could shorten menstruation cycle from 76 days to 41 days.